2017
DOI: 10.4103/jpn.jpn_87_17
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and outcome of acute neurologic complications after congenital heart disease surgery

Abstract: Objectives:To determine the frequency and immediate outcome of acute neurologic complications (ANCs) in children undergoing congenital heart surgery (CHS).Materials and Methods:In this retrospective study, all patients undergoing CHS at our hospital from January 2007 to June 2016 were included. Patients were followed up for the development of seizures, altered level of consciousness (ALOC), abnormal movements, and stroke. Results are presented as mean with standard deviation and frequency with percentages.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Jafri et al reported that 35 (1.75%) of the 2000 pediatric cardiac surgery patients they evaluated developed acute neurological complications, and 28 of those 35 patients (80%) presented clinical signs of seizure [ 4 ]. Of the 3849 patients who underwent surgery, 162 had neurological complications in the early period, comprising a rate of 4.2% in our patient group; 42.6% of these 162 patients ( n = 69) had seizures, 10.5% ( n = 17) had confusion, 24.1% ( n = 39) had stupor symptoms, and 22.8% ( n = 37) demonstrated symptoms of hemiparesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jafri et al reported that 35 (1.75%) of the 2000 pediatric cardiac surgery patients they evaluated developed acute neurological complications, and 28 of those 35 patients (80%) presented clinical signs of seizure [ 4 ]. Of the 3849 patients who underwent surgery, 162 had neurological complications in the early period, comprising a rate of 4.2% in our patient group; 42.6% of these 162 patients ( n = 69) had seizures, 10.5% ( n = 17) had confusion, 24.1% ( n = 39) had stupor symptoms, and 22.8% ( n = 37) demonstrated symptoms of hemiparesis.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative neurological problems are also seen in children with congenital heart disease, regardless of surgical complications. It should be kept in mind that abnormal brain development, chromosomal and genetic anomalies, and sequelae such as thin and coarse motor deficits secondary to previous medical interventions, attention deficit hyperactivity disorder, and speech and language disorders may develop [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Congenital heart disease is a further reason for critical illness in early infancy in up to 0.8 % of livebirth. Survival improved due to early heart surgery but there is a significant burden of neurodevelopmental deficits: Acute neurologic complications in children undergoing congenital heart surgery occur in 1.75% patients in a recent retrospective study and are related to hypoxia, brain bleeding or embolism [23]. The cumulative incidence rates of attention deficit (hyperactivity) disorder and autism spectrum disorder were even higher in children with congenital heart disease than in a control group (4.55 vs. 1.26/1000 person years for attention deficit hyperactivity disorder and 0.99 vs.0.2/1000 person-years for autism spectrum disorder) [24].…”
Section: Hyothermia and Hrvmentioning
confidence: 99%
“…As per neuroimaging and psychological evaluations, the surveys suggest that cardiac anomalies can precipitate impaired neurocognitive function. It is marked by changes in multiple areas, including diminished brain power, an increased risk of seizure or stroke, and an altered level of consciousness (ALOC), 7 , or diminishing IQ as a result of chronic or prolonged hypoxia and cyanotic lesions. However, our point of focus in this study is the outcome of attention-deficit/hyperactivity disorder (ADHD) as a late complication in CHD patients.…”
Section: Introductionmentioning
confidence: 99%